Study Of Risk, Capitalization And Efficiency In Malaysian Commercial Banks - Yan, Yap Liang (2007)
This study intends to investigate the impact of merger on certain aspect of the banking sector. One aspect of the study is to investigate the impact of merger on the cost efficiency of banks in Malaysia. To this extent, an effort is made to determine if the merger of banks actually improved profitability across the banking sector. In addition, the study also attempts to determine the relationship between cost efficiency, risk taking and capitalisation of banks.